Stella Demesticha and Lucy Blue with Calliope Baika, Carlo Beltrame, David Blackman, Deborah Cvikel, Helen Farr and Dorit Sivan. Under the Mediterranean I: Studies in Maritime Archaeology. (Honor Frost Foundation Research Publication 1). / Elpida Hadjida - Wallace, Saro (Journal of Greek Archaeology, 2023)
pp. 396. Leiden: Sidestone Pres,. 2021. ISBN 978-90-8890-945-0 paperback. £85.00. / pp. 94. INSTAP Prehistory Monographs. Philadelphia: INSTAP Academic Press, 2021. ISBN 9781931534291 hardcover. £54.00.